Karbon Tersimpan Analisis Komposisi Dan Potensi Cadangan Karbon Tersimpan Pada Vegetasi Penyusun Riparian Sungai Pusur Kabupaten Klaten: Analysis Of Composition and Potential Carbon Stock Stored in Riparian Vegetation Pusur River in Klaten District - Woesono, Hastanto Bowo; Wahyudiono, Sugeng; Telaumbanua, Imelda Kristy (HUTAN TROPIKA, 2024)
The quantity of biomass in the forest is the result of the difference between production through photosynthesis and consumption by respiration and harvesting processes. This study aims to determine the types of vegetation, vegetation composition and potential carbon stocks at various altitudes. This study used a quantitative survey method, to obtain and collect vegetation information data along the riparian of the pusur river. The conclusion of the types of vegetation that make up the Pusur River Riparian is 36 types of understory plants, 8 types of seedlings with a diameter of less than 5 cm, 17 types of trees with a diameter of 5-20 cm, 21 types of trees with a diameter of 20-50 cm, 7 types of trees with a diameter above 50 cm. The composition of vegetation types that make up the Pusur River Riparian is 1,239 individual understory plants, 33 seedlings less than 5 cm in diameter, 85 trees 5-20 cm in diameter, 104 trees 20-50 cm in diameter, and 14 trees above 50 cm in diameter. The potential carbon stock stored in the vegetation that makes up the Pusur River Riparian is in block 1 upland as much as 395.24 tons, block 2 middle land as much as 309.36 tons and block 3 lowland as much as 360.98 tons, with a total along 26 km of 1,065.57 tons, and for those that are likely to be lost due to commercial timber species is 701.63 tons or equivalent to 65.85% of the total carbon.